Progression-free survival and overall survival in patients with advanced HER2-positive breast cancer treated with trastuzumab emtansine (T-DM1) after previous treatment with pertuzumab - Michel, Laura L.; Wallwiener, Markus; Schneeweiss, Andreas (Cancers, 2020)
The approval of trastuzumab emtansine (T-DM1) was conducted without pertuzumab as previous therapy. Efficacy data on T-DM1 following pertuzumab treatment are therefore limited. This study explores this issue in a real-world setting. Within the prospective PRAEGNANT (Prospective Academic Translational Research Network for the Optimization of the Oncological Health Care Quality in the Advanced Setting) metastatic breast cancer registry (NCT02338167), patients in all therapy lines receiving any kind of treatment were eligible for inclusion. This report describes patient characteristics and progression-free survival (PFS) in human epidermal growth factor receptor 2 (HER2)-positive patients receiving T-DM1 after pertuzumab treatment. Seventy-six patients were identified, 39 of whom received T-DM1 as second-line therapy, 25 as third-line, and 12 as fourth-line therapy or higher. Pertuzumab was mostly administered as a first-line treatment (n = 61; 80.3%). The median PFS in all patients was 3.5 months (95% CI: 2.8–7.8); in second-line treatment, 7.7 months (95% CI: 2.8–11.0); in third-line, 3.4 months (95% CI: 2.3–not reached (NR)); and in fourth-line therapy or higher, 2.7 months (95% CI: 1.2–NR). T-DM1 was mainly administered second-line after pertuzumab, but also in more heavily pretreated patients. The PFS in higher therapy lines appears to be shorter than in second-line.
Gesehen am 03.12.2020